Effectiveness of USG-guided corticosteroid injection administered into the glenohumeral joint and oral prednisone treatment in patients with adhesive capsulitis (Annals of Medical Research, 2024)
Aim: This study aims to compare the efficacy of ultrasonography-guided corticosteroid injection to the glenohumeral joint and oral steroid therapy on clinical response and inferior axillary pouch (AR) thickness measured by ultrasonography (USG) in patients with adhesive capsulitis (AC).Materials and Methods: Our prospective randomized study included 48 patients (18-65 years) with a diagnosis of AC. The first group (n=24) underwent USG-guided corticosteroid injection to glenohumeral joint. In the second group (n=24), oral prednisone was started at 0.5 mg/kg dose with the dosing schedule determined by decreasing and continued for 6 weeks. Both groups were also included in a standard physical therapy program (electrotherapy+exercises). The questionnaire, active and passive shoulder joint range of motion (ROM) measurements, Shoulder Pain and Disability Index (SPADI), evaluation of the joint with USG, and AR thickness measurements were performed.Results: There was a statistically significant increase in passive-active ROM values in all directions before and after the treatment (p
Keywords: Adhesive capsulitis; Ultrasound; Steroid; Axillary (inferior) pouch